Clinical, haematological and pathological investigations of Escherichia vulneris in rainbow trout (Oncorhynchus mykiss) - Aydın, Seyit; Çelebi, Selahattin (Fish Pathology, 32 (1), 29-34,1997.3, 1997)
Escherichia vulneris was isolated from naturally infected rainbow trout Oncorhynchus mykiss, balloon moly Poecilia sp., silver moly Poecilia sp., and Caucasian carp Carassius carassius, and its pathogenicity was tested by intramuscular injection using healthy I.S-year-old rainbow trout. The experimental infection caused mortalities with gross clinical and histopathological abnormalities in tissues of epidermis, gills, liver, kidney, spleen and intestine of the fish. Leucocytes, lymphocytes and granulocytes in blood of the infected fish were significantly increased as compared to healthy fish and/or recovered fish. Other blood parameters such as haemoglobin content haematocrit value, thrombocyte and erythrocyte numbers were not significantly different between the experimentally infected and healthy. In a therapeutic experiment injection with oxytetracycline controlled the infection.
Keywords: Bacterial diseases, haematology, hisopathology, Escherichia vulneris, rainbow tront, balloon moly, silver moly, Caucasian carp